Papel da hidrólise extracelular de ATP na imunossupressão, resistência à quimioterapia e invasividade dos gliomas - Scheffel, Thamiris Becker (2022)
Gliomas are extremely aggressive. Tumor malignancy has been attributed to several mechanisms of resistance to therapy that include the intense immunomodulatory capacity and the invasion of the underlying tissue. It is suggested that purines and pyrimidines may act as signaling molecules, influencing such characteristics. ATP hydrolysis by ectonucleoside triphosphate diphosphohydrolases (E-NTPDases) and the consequent formation of adenosine are related to the positive regulation of proliferation, migration, cell survival and inhibitory immunological checkpoints such as the PD-1/PD-L1 pathway. Thus, the hypothesis of this study is that the inhibition of ATPase activity would result in the reduction of immunosuppression, resistance to chemotherapy and tumor invasiveness, directly or indirectly through action on the tumor microenvironment. The synergistic action of the adenosine pathway and the PD-1/PD-L1 axis maintaining immunosuppression in gliomas was described in this study. The involvement of these pathways in the progression of gliomas is well known. In this context, the inhibition of adenosine formation together with the favoring of high concentrations of extracellular ATP could increase the antitumor landscape in the tumor microenvironment and minimize the tumor mechanisms of resistance to therapy. The use of the E-NTPDase inhibitor polyoxometalate-1 (POM-1) was shown to be related to the potentiation of the effect of temozolomide, through the reduction of cell viability and induction of apoptosis in glioblastoma cells (GBM). Furthermore, the analysis of the invasive-migratory potential of GBM cells was evaluated in a 3D culture model using the migratory fitness method, developed throughout this work. Inhibition of extracellular ATP hydrolysis favored the occurrence of a less invasive cellular phenotype, reducing the mass of migrating cells. Based on in vitro findings, the effect of POM-1 was evaluated in a pilot study of GBM murine model that involved intranasal administration of the inhibitor and demonstrated a strong tendency to increase inflammation at the tumor site and reduce lymphocyte infiltration of regulatory T cells, which characterizes reduced immunosuppression. Overall, this work demonstrates tumor microenvironment modulation strategies that weaken temozolomide resistance mechanisms and minimize the invasiveness of extremely malignant tumors.